Characterization and origin of dunitic rocks in the Ni-Cu-(PGE) sulfide ore-bearing Kevitsa intrusion, northern Finland: whole-rock and mineral chemical constraints - Luolavirta, K.; Hanski, E.; Maier, W.; Santaguida, F. (Bulletin of the Geological Society of Finland, 2018)
The ca. 2.06 Ga Kevitsa intrusion is one of the ore-bearing mafic-ultramafic igneous bodies in the Central Lapland greenstone belt. A large disseminated Ni-Cu-(PGE) sulfide ore deposit is hosted by olivine-pyroxene cumulates in the lower ultramafic part of the intrusion, indicating involvement of a multiply saturated magma in the ore formation. There are also various dunitic rocks, which occur as numerous inclusions within the Kevitsa intrusion, most commonly in the economic resource area. On textural basis, two distinct types of inclusions are recognized: i) cumulate-textured (Kevitsa Dunite) and ii) recrystallized ultramafic inclusions. In addition, there also exists a separate dunitic body (Central Dunite) with a suface area of 0.6 x 1.0 km, cropping out in the central part of the intrusion. The Central Dunite and Kevitsa Dunite are similar olivine-chromite cumulates and with comparable whole-rock and mineral compositions, suggesting that they are cogenetic. A magmatic, rather than replacement origin for the dunitic cumulates is evidenced by their systematic mineral compositional trends consistent with magmatic fractionation. Wholerock major and trace element and mineral compositional data of the dunitic cumulates and Kevitsa olivine pyroxenites fall on the same linear trends and record similar REE characteristics indicating a genetic link between these two. The parental magmas for the dunitic cumulates were probably picritic and related to the picritic and basaltic volcanic rocks in the area. The high Fo content of olivine (up to ~89 mol.%) is consistent with a high- Mg parental melt. The recrystallized ultramafic inclusions are fine-grained and show a granoblastic/interlobate textures indicative for thermal textural readjustment. Two subgroups are identified: Group 1 shows a chemical affinity towards the dunitic cumulates and are interpreted as their recrystallized clasts. The Group 2 inclusions are compositionally comparable to the ~2.06 Ga komatiitic volcanic rocks in the area and are considered as ...